THE EFFECT OF PRODUCTION, PRICE, AND EXCHANGE RATE ON EXPORT VOLUME (STUDY ON INDONESIAN COCOA BEAN EXPORT VOLUME FOR THE PERIOD JANUARY 2019-DECEMBER 2022) - Muhammad Dwiky Reza; Marko S Hermawan (Journal of Social Research, 2024)
This study aims to determine the Effect of Production, Price, and Exchange Rate on the Export Volume of Cocoa Beans in Indonesia for the January 2019 – December 2022 Period in Jakarta. Data collection was carried out in descriptive quantitative research by distributing offline questionnaires to 100 respondents who knew cocoa beans in Indonesia with those domiciled in Jakarta. Data analysis was processed using multiple regression calculations through SPSS version 22. The results obtained from this study are Production (X1), Price (X2), and Exchange Rate (X3) have a significant influence on Export Volume (Y) either partially or stimulantly